The California Breast Cancer Survivorship Consortium (CBCSC): prognostic factors associated with racial/ethnic differences in breast cancer survival - Anna H. Wu; Scarlett Lin Gomez; Cheryl Vigen; Marilyn L. Kwan; Theresa H. M. Keegan; Yani Lu; Salma Shariff-Marco; Kristine R. Monroe; Allison W. Kurian; Iona Cheng; Bette J. Caan; Valerie S. Lee; et al. (Cancer Causes & Control, 2013)

In situ activity of a dominant P rochlorococcus ecotype ( eHL ‐ II ) from rRNA content and cell size - Yajuan Lin; Katrina Gazsi; Veronica P. Lance; Alyse A. Larkin; Jeremy W. Chandler; Erik R. Zinser; Zackary I. Johnson (Environmental Microbiology, 2013)
Summary In the open ocean genetically diverse clades of the unicellular cyanobacteria P rochlorococcus are biogeographically structured along environmental gradients, yet little is known about their in situ activity. To address this gap, here we use the numerically dominant P rochlorococcus clade e HL ‐ II (e MIT 9312) as a model organism to develop and apply a method to examine their in situ activity using r RNA content and cell size as metrics of cellular physiology. For two representative isolates ( MIT 9312 and MIT 9215) r RNA cell −1 increases linearly with specific growth rate but is anticorrelated with cell size indicated by flow cytometrically measured ( SSC ). Although each strain has a unique relationship between cellular r RNA (or cell size) and growth rate, both strains have the same strong positive correlation between r RNA cell −1 SSC −1 and growth rate. We field test this approach and observe distinct patterns of eHL ‐ II clade specific activity (r RNA cell −1 SSC −1 ) with depth that are consistent with patterns of photosynthetic rates. This molecular technique provides unique insight into the ecology of P rochlorococcus and could potentially be expanded to include other microbes to unravel the ecological and biogeochemical contributions of genetically distinct marine side scatter microbes.

Soluble interleukin‐1 receptor, a potential negative regulator of orange‐spotted grouper Epinephelus coioides interleukin‐1 system - D. Q. Lu; M. Yao; S. B. Yi; Y. W. Li; X. C. Liu; Y. Zhang; H. R. Lin (Journal of Fish Biology, 2013)
In this study, the cDNA sequence encoding interleukin‐1 ( Il ‐1) receptor‐like protein of orange‐spotted grouper Epinephelus coioides was obtained. The newly identified sequence was named soluble type I Il ‐1 receptor ( sIl‐1rI ) owing to its structural composition, which had two Ig‐like domains, lack of transmembrane region and the Toll/interleukin‐1 receptor ( TIR ) domain, similar to the brown rat Rattus norvegicus soluble Il‐1rI . In addition, sequence comparison and phylogenetic analysis indicated that E. coioides sequence had a closer relationship with Il‐1rI than Il‐1rII . Real‐time PCR revealed that sil‐1rI mRNA expression presented a process of decrease, restoration and increase in Cryptocaryon irritans ‐infected E. coioides . The negative correlation between Il ‐1β and sil‐1rI mRNA in C. irritans ‐infected head‐kidney implied the potential negative regulatory role of sil‐1rI in E. coioides Il ‐1 system. The leucocytes incubated with lipopolysaccharide or polyriboinosinic polyribocytidylic acid exhibited different expression profiles of sil‐1rI . Recombinant Il ‐1β ( rIl ‐1β) protein was capable of inducing sil‐1rI mRNA under the concentration of 100 ng ml −1 , suggesting that high dosage or excess Il ‐1β would stimulate the expression of sil‐1rI to maintain the homoeostasis of E. coioides Il ‐1 system. For the first time, the role of teleost Il‐1rI in parasite infection has been identified, and soluble Il‐1r was found in fish.

Warming up to climate change: a participatory approach to engaging with agricultural stakeholders in the Southeast US - Wendy-Lin Bartels; Carrie A. Furman; David C. Diehl; Fred S. Royce; Daniel R. Dourte; Brenda V. Ortiz; David F. Zierden; Tracy A. Irani; Clyde W. Fraisse; James W. Jones (Regional Environmental Change, 2013)

Selenoprotein P and Yunnan Endemic Sudden Cardiac Death—an Ecological Study - Q. Li; X. Z. Li; T. Wang; L. W. Zhou; H. Q. Feng; L. Gao; J. R. Pei; C. Lin; C. X. Jiang (Biological Trace Element Research, 2013)